To solve the system of equations using the elimination method, we need to eliminate one of the variables. Here are the two equations we have:
- \( 2x - 3y = 14 \) (Equation 1)
- \( 4x + 3y = 10 \) (Equation 2)
Step 1: Align the equations.
We can add Equation 1 and Equation 2 directly since the coefficient of \( y \) in Equation 1 is \( -3 \) and in Equation 2 is \( +3 \). This means that if we add the equations, the \( y \) terms will cancel out.
Step 2: Add the equations.
\[ (2x - 3y) + (4x + 3y) = 14 + 10 \]
This simplifies to:
\[ 2x + 4x - 3y + 3y = 24 \]
\[ 6x = 24 \]
Step 3: Solve for \( x \).
\[ x = \frac{24}{6} = 4 \]
Step 4: Substitute \( x \) back into one of the original equations to solve for \( y \).
We can use Equation 1:
\[ 2(4) - 3y = 14 \]
This simplifies to:
\[ 8 - 3y = 14 \]
Subtract 8 from both sides:
\[ -3y = 14 - 8 \] \[ -3y = 6 \]
Now, divide by -3:
\[ y = \frac{6}{-3} = -2 \]
Final Answer:
The solution to the system of equations is:
\[ (x, y) = (4, -2) \]